2005
DOI: 10.1080/00913367.2005.10639194
|View full text |Cite
|
Sign up to set email alerts
|

Sponsorship-Linked Marketing: Opening the Black Box

Abstract: Sponsorship of sports, arts, and causes has become a mainstream marketing communications tool. A great deal of fieldwork has attempted to gauge the relative effectiveness of sponsorship in a marketing context, but these weakly controlled field studies contribute little to our understanding of how individuals process sponsorship-linked marketing communications. By considering possible underlying information-processing mechanics, individual-and group-level factors, market factors, and management factors, togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
397
1
15

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 503 publications
(436 citation statements)
references
References 79 publications
9
397
1
15
Order By: Relevance
“…In communications regarding sponsor-event pairings, mentioning competitors can produce memory interference and thereby reduce recall for the true sponsor (Johar and Pham 1999). Various individual factors such as involvement with the sponsored event can also influence recall (see Cornwell, Weeks, and Roy 2005); however, the variable most frequently researched in conjunction with memory for the sponsorship relationship has been congruency between the sponsor and event. Congruency is thus reviewed briefly.…”
Section: Conceptual Development: Establishing a Link In Memorymentioning
confidence: 99%
“…In communications regarding sponsor-event pairings, mentioning competitors can produce memory interference and thereby reduce recall for the true sponsor (Johar and Pham 1999). Various individual factors such as involvement with the sponsored event can also influence recall (see Cornwell, Weeks, and Roy 2005); however, the variable most frequently researched in conjunction with memory for the sponsorship relationship has been congruency between the sponsor and event. Congruency is thus reviewed briefly.…”
Section: Conceptual Development: Establishing a Link In Memorymentioning
confidence: 99%
“…Furthermore, perceived alignment of sponsor and sponsored club is one central dimension in the "Brand Image Transfer" model proposed by Smith (2004). This strategic fit between the sponsor and sponsee has in a number of studies been shown to be an important dimension in generating a favourable attitude towards the sponsor (Becker-Olsen and Hill, 2006;Cornwell et al, 2005;Donlan, 2014;Grohs et al, 2004;Lacey and Close, 2013;Woisetschläger et al, 2017;Zaharia et al, 2016). A lack of fit, e.g.…”
Section: Football Clubs As Mediatorsmentioning
confidence: 99%
“…The reason for this is an understanding that positive effects from a sponsorship are dependent on long-term rather than short-term objectives in brand management. Even though it has been shown that typical shirt sponsor programmes are based on expectations on short-term returns (Chadwick and Thwaites, 2006), sponsorships of team-based sports with a large fan base are most likely concerned with long-term brand identification (Cornwell et al, 2005). …”
Section: Literature Reviewmentioning
confidence: 99%
“…The increased media coverage is also one reason that approximately two-thirds of all sponsorship spending is directed at sporting events, leagues, teams, and players (Crompton, 2004;Verity, 2002), although there is also increasing interest in cultural sponsorships (Irwin et al, 2003;Menon and Kahn, 2003;Polonsky and Wood, 2001;Quester and Thompson, 2001;Rifon et al, 2004;Ruth and Simonin, 2003;Simmons and Becker-Olsen, 2006). While sponsoring is an increasingly important communication tool, relatively few attempts have been made to measure and understand the effects of sponsorship (Cornwell, et al, 2005;Meenaghan, 2001;Quester and Thompson, 2001;Thjømøe et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…brand or firm) providing cash and/or other compensation in exchange for access to an object's commercial potential (i.e. exposure and association with the cause, event, organization or individual related to a sport, cultural, and/or non-profit entity) (Cornwell et al, 2005). Annual world-wide spending on sponsorships has grown rapidly to an estimated $33+ billion (Akaoui, 2007), due in part to such factors as increasing restrictions on advertising, higher advertising costs, zapping, and increased media coverage of sponsored events (Quester and Thompson, 2001;Speed and Thompson, 2000;Verity, 2002).…”
Section: Introductionmentioning
confidence: 99%